Cesarean Section in the Delivery Room: An Exploration of the Viewpoint of Midwives, Anaesthesiologists, and Obstetricians. (27th September 2018) - Jolien, Jansegers; Yves, Jacquemyn
Abstract : Aim . To explore the attitude and vision of midwives, anaesthesiologists, and obstetricians concerning a dedicated operating room for cesarean sections within the delivery ward versus cesarean sections within the general operating room. Method . A descriptive qualitative study using a constructive paradigm. Face-to-face semistructured interviews were performed in 3 different hospitals, one without operating theatre within the delivery ward, one with a recently built cesarean section room within the delivery ward, and one with a long time tradition of cesarean section in the delivery room. Interviews have been analysed thematically. Results . Three themes have been identified: organization, role of the midwife, and safety. Although identical protocols for the degree of emergency of a cesarean section are used, infrastructure and daily practice differ between hospitals. Logistic support, medical and midwife staffing, and hospital infrastructure are systematically mentioned as needing improvement. Realizing cesarean section within the delivery ward was considered as an improvement for the patient's experience. Midwives need a clear and new job description and delineation and mention a lack of formal education to assist surgical procedures. To increase patient safety continuous education and communication are considered necessary. Conclusion . A detailed job description and education of all those involved in cesarean section at the delivery ward are necessary to improve patient safety. Patient experience is improved, but our knowledge on this is hampered by lack of studies.